I-ST INTERNATIONAL CONFERENCE. "PINK TOMATO. PRODUCTION. CONSUMPTION. MARKET TRENDS IN CENTRAL ASIA». - Sh. Alimov; M. M. Tareeva (Овощи России)
28 May 2015, in Tashkent, Uzbekistan, the Ist International conference "Pink tomato. Production, consumption, market trends" was held. The problems of breedong, seed production of cultivars and hybrids of pink tomato, as well as increasing of consumer's demand have been considered. The conference has provided good opportunity for meetings of producers, breeders, and researchers from different countries.